OJT Performance and Competencies of BSA Students in the City College of Calamba: Basis for OJT Training Manual - Rosario, Jomar; Lanuza, Maryann; Aligam, Neil; Almoro, Ellen (Journal of Interdisciplinary Perspectives, 2025)
In today's dynamic and ever-evolving educational landscape, one of the most effective and well- recognized methods for educating students in the information and abilities required to operate in a professional setting is on-the-job training (OJT). A lack of OJT frequently diminishes the likelihood of a seamless transition from college to the workforce. Many businesses, therefore, provide OJT to students before hiring them for full-time jobs, hence this study enabled us to determine the OJT performance of the Bachelor of Science in Accountancy (BSA) students in six areas namely: Attendance; Communication skills; Collaboration, and teamwork; Problem-Solving; Work Ethics; and Time Management. Also, the study described the level of competencies the interns have in terms of Training Skills, adaptability, Critical thinking, and Attitude. The sixty-six (66) employers of the interns evaluated the areas after they finished their OJT work hours. Employers evaluated a very satisfactory overall OJT performance and an outstanding BSA Competency. Strong Correlations existed between the BSA competencies and how they perform in the six areas of OJT performance, from attendance to time management. It only implies that the college has to continue developing the competencies so that they will be reflected in their internship performance in the field. By investing in these techniques and programs, the institution can help BSA students grow academically and succeed in their future employment. When they graduate, they will have good cooperation abilities, be more capable of negotiating complicated work situations, inspire creativity, and create collective success in their chosen professions. Hence, all strong areas for sustainability were included in the draft of the institution's OJT Manual as it has proven to have a strong capacity to increase employability once the OJT graduates.